EDUCATIONAL PHILOSOPHY AS A FOUNDATIONAL FRAMEWORK FOR THE CHARACTER DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS - Ajeng Tri Agustini; Yusuf Tri Herlambang; Yeni Yuniarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Character formation among elementary school students has become a crucial necessity amid the challenges of the digital era. Schools, families, and communities play a significant role in shaping children’s morality; therefore, a clear philosophical foundation is required to guide the process of character education. This study aims to examine the role of educational philosophy as a basis for the development of moral and ethical values in elementary school students through a review of recent literature. The method employed was a Systematic Literature Review of national and international articles published between 2022 and 2025, selected through the PRISMA stages. The findings indicate that character education is effective when moral values are integrated into the curriculum, teachers act as moral exemplars, active learning is implemented, and families as well as the school environment provide consistent support. Educational philosophy offers a conceptual direction that assists teachers in adjusting learning strategies to the students’ contextual conditions. In conclusion, character education becomes more meaningful when it is grounded in philosophical principles that emphasize values, reflection, and authentic learning experiences.